OPTIMIZED AREA AND SPEED ARCHITECTURES FOR THE MIX COLUMN OPERATION OF THE ADVANCED ENCRYPTION STANDARD (International Journal of Food and Nutritional Sciences, 2021)
This project plays vital role in all type of communication applications. This project designs anovel low-transition linear feedback shift register (LFSR) that is based on some new observations aboutthe output sequence of a conventional LFSR. Security of a hardware implementation can be compromisedby a random fault or a deliberate attack.